The Entity Concept. - Berg, Kenneth B.; Blakely, Edward J.; Johnston, Kenneth S.; Westfall, Other D.; Windal, Floyd W.; Sprouse, Robert T. (The Accounting Review, 1965)
Abstract This article explores the business entity concept of the 1964 Concepts and Standards Research Committee of the American Accounting Association and its significance to accounting. The committee's study of the business entity concept has caused it to depart significantly from the concise statement of the concept contained in the 1957 Revision. The committee believes that in referring to concepts underlying the conventions of accounting the use of the term business is inappropriately restrictive. The committee suggests that, in accounting, the term entity concept be used. In accounting the entity with which one is concerned may be defined as an area of economic interest to a particular individual or group. The boundaries of such an economic entity are identifiable by determining the interested individual or group, and by determining the nature of that individual's or that group's interest. An economic entity encompasses the activities, events, and utilization of resources that affect the interest of the individual or group. Simply stated, the committee advocates a user-oriented approach in defining an entity. That is, accounting reports about entities are developed to meet the needs of particular individuals or groups.